2017
DOI: 10.7717/peerj.3259
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and cardio-metabolic risk factors in patients with Obstructive Sleep Apnea: cross-sectional study

Abstract: BackgroundLittle is known about the role of dietary intake in obstructive sleep apnea (OSA), which could prove important in improving clinical outcomes for people with obesity and/or cardiovascular disease within these populations. Reduction in energy intake typically results in weight loss, markedly improving metabolic parameters and ameliorating OSA severity. The aim of this study was to evaluate the association of dietary and cardio-metabolic risk factors with OSA severity.MethodsThis was a cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
0
6
1
1
Order By: Relevance
“…This meta‐analysis investigated the available evidence on the association between OSA and alcohol, caffeine and tobacco. Studies indicate associations between tobacco and OSA, and alcohol and OSA, however, conclusive evidence was not found until now. Based on the current available literature and on the eligibility criteria established for this systematic review, results indicate OSA is to be associated with the use of alcohol, but there is not enough scientific evidence to confirm the association between OSA and tobacco.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This meta‐analysis investigated the available evidence on the association between OSA and alcohol, caffeine and tobacco. Studies indicate associations between tobacco and OSA, and alcohol and OSA, however, conclusive evidence was not found until now. Based on the current available literature and on the eligibility criteria established for this systematic review, results indicate OSA is to be associated with the use of alcohol, but there is not enough scientific evidence to confirm the association between OSA and tobacco.…”
Section: Discussionmentioning
confidence: 92%
“…Alcohol was too associated with significant increases arterial oxygen desaturation and the number of apneic events in healthy men . Stelmach‐Mardas et al showed that a higher intake of alcohol was significantly associated with increased odds of being in an OSA category of higher severity as compared to non‐OSA (OR = 1.03, 95%CI = 1.01‐1.04).…”
Section: Discussionmentioning
confidence: 99%
“…People diagnosed with SA are at higher risk to develop hypertension, metabolic disorders, and neurodegenerative disorders, such as Alzheimer’s disease (AD) and Parkinson’s disease (PD) (Grandner, 2017; Kapur et al, 2002; Lavie and Lavie, 2009; Saaresranta et al, 2016; Shao et al, 2015; Stelmach-Mardas et al, 2017; Yeh et al, 2016). Key characteristics of all these disorders include inflammation, oxidative stress, and, in men, low testosterone (reviewed in (Dai et al, 2014)).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we hypothesized that the effects of CPAP were high in groups that had metabolic dysfunction or central nervous system resistance to leptin's ventilation promoting effect. We also hypothesized that these groups could have reduced cardiovascular risk [20][21][22].…”
Section: Consequences For Clinical Practicementioning
confidence: 99%